A leitura do feminino em Anne de Green Gables e Anne com e - Marques, Jéssica Souza Ferreira (2023)
This study aims to investigate the retextualization of the feminine in Anne of Green Gables (2019) in the first season of the series Anne with an E (2017). This book was written by Lucy Maud Montgomery and published for the first time in 1908 in Canada, the choosen edition for was published in Brazil in 2019 and covers the story of the character Anne Shirley and her experiences. The series titled Anne with an E is an intersemiotic adaptation created by Canadian Moira Walley-Beckett and made available on the Netflix streaming platform. The character Anne Shirley provides readers and viewers with messages of change, reflection and action; So, what is the interpretation of the feminine in the book and in the television series? The methodology used was the qualitative analysis of objects through bibliographical research, using the following theories: Tradução Intersemiótica (Plaza, 2010); Teoria da Adaptação (Hutcheon, 2013); Intermidialidade (Clüver, 2011); Estudos femininos (Hooks, 2022); Memória (Bosi, 2022) e (Elias, 1998). It is fundamental to organize the analysis into subtopics: Society, Education and Culture, highlighting the fictional city of Avonlea as the focus. The raised questions are: How are women represented in society? What is the perspective regarding female education? What are the social behaviors presented in the corpus? The results obtained were: the importance of intersemiotic translation in establishing links between cultures, promoting the dissemination of information, ideologies, stories. In addition to introducing the presentation of the main character as a vanguard in her socio-historical context. As per conclusion, it is necessary to investigate and translate Montgomery's writings in Brazil.